The Bishop Murderer. Issue 1 (1st January 2019) - Adams, Jonathan
ABSTRACT: This article presents and discusses a parchment fragment in the Royal Library in Copenhagen (Fragment Collection, no. 3230), a single folio of a now lost manuscript. It contains a miracle tale about a bishop murderer, a story that can also be found in the famous edifying work Consolation of the Soul . The medieval Danish translation of Consolation of the Soul – Sjælens trøst – is extant in two separate pieces (Ups. C 509 and Holm. A 109) of what was once a single manuscript. The two separate pieces do not, however, make a whole and part of the Sjælens trøst manuscript is missing. However, the Copenhagen fragment is not part of this missing piece. In fact, it belongs to an entirely different text tradition – Étienne de Bourbon's Tractatus de diversis materiis praedicabilibus – and is a remnant of a translation of (part of) this collection of exempla. As such, it is a significant addition to our knowledge of medieval preaching in Denmark and the use of vernacular translations of continental, Latin didactic material in exempla.